A Transdiagnostic Multilevel Examination of Interoceptive Processing in Individuals With a Remote History of Suicidal Behavior. Issue 5 (September 2021) - DeVille, Danielle C.; Khalsa, Sahib S.; ,; Lapidus, Rachel C.; White, Evan; Paulus, Martin P.; Aupperle, Robin L.
Highlights: Interoception was assessed in remote suicide attempters and nonattempters. Interoception was measured using a battery of behavioral measures. Remote suicide attempters had higher pain tolerance on a cold-pressor task. Remote suicide attempters reported less suffocation on a breath-hold task. Suicide attempters may exhibit persistent aversive interoceptive processing deficits. Abstract: A developing area of research suggests that there may be a relationship between interoception and suicidal behavior. For example, it was recently reported that individuals who made a suicide attempt within the previous 5 years exhibit behavioral and neural abnormalities across multiple domains of interoception relative to nonattempters. This included increased tolerance for aversive sensations of pain and dyspnea, reduced heartbeat-perception accuracy, and blunted insula activity during attention to cardiac sensations. However, the degree to which interoceptive deficits persist following a suicidal attempt is unknown. In the current study, we examined differences between individuals with a remote history of suicide attempts (greater than 5 years ago; N = 56) versus those with no history of attempts ( N = 240). We found that remote suicide attempters demonstrated greater pain tolerance and lower ratings of stress during a cold-pressor challenge and lower ratings of suffocation during a breath-hold challenge, as compared to nonattempters. In contrast, there were no group differences in breath-hold duration, interoceptive accuracy on a heartbeat-tapping task, or insula activation during cardiac attention. An exploratory resting-state functional connectivity analysis of individuals with suicide attempts in the past 5 years ( N = 23), individuals with more remote histories of suicide attempts ( N = 39), and nonattempters ( N = 232) revealed preliminary and subtle evidence of differences in insula connectivity with areas of the temporal cortex in remote suicide attempters. Taken together, these findings suggest that blunted affective responses to aversive interoceptive sensations is an enduring characteristic of suicide attempters, even when assessed many years after a suicide attempt, whereas differences in the experience of nonaversive interoceptive sensations may be less persistent.